2013
DOI: 10.1080/20742835.2013.11441215
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sampling methods for cervical cancer screening: practical perspectives from the laboratory

Abstract: The coverage of cervical cancer screening in South Africa is inadequate, with an estimated 8.8-million unscreened women who are mainly serviced by the public health sector in lower-resourced areas. Alternative screening options need to be considered. Every step in the screening process needs to be critically evaluated to design a practical programme without a bottleneck, to deliver maximum benefit with limited available resources. Patient self-sampling has been identified as an acceptable method of specimen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The method and main results of this study have previously been reported. 4,19,20 Based on the wide age range, the estimated HIV prevalence of this group was between 19% and 33%.…”
Section: Settingmentioning
confidence: 99%
“…The method and main results of this study have previously been reported. 4,19,20 Based on the wide age range, the estimated HIV prevalence of this group was between 19% and 33%.…”
Section: Settingmentioning
confidence: 99%
“…In the first article in this supplement, Richter investigates alternative screening options, such as patient self-sampling combined with high-risk human papillomavirus (HPV)based testing, which has the potential to increase cervical cancer screening coverage, especially in areas in which screening is inadequate. 1 The article focuses on sample collection, transportation, preparation, testing and the interpretation of the results. As the virologist in charge of the CANSA-funded study, Dr Richter was intimately involved in these aspects and provides a personal perspective.…”
mentioning
confidence: 99%